REPRESENTASI POLITIK IDENTITAS DALAM PEMILIHAN PRESIDEN 2019 PADA PEMBERITAAN KOMPAS.COM (Fakultas Dakwah dan Komunikasi, 2020)
This study aims to determine the representation of identity politics in the 2019 presidential election in Kompas.com. This scientific research approach uses framing analysis by Robert N Entman, who will look at what the mass media frame each report and also what journalists look at in selecting the issue and also the viewpoint used. the results show that Kompas.com in viewing the issue of identity politics as a threat to the unity and harmony of the multicultural Indonesian people. Kompas.com puts identity politics in the form of straight news.This study aims to determine the representation of identity politics in the 2019 presidential election in Kompas.com. This scientific research approach uses framing analysis by Robert N Entman, who will look at what the mass media frame each report and also what journalists look at in selecting the issue and also the viewpoint used. the results show that Kompas.com in viewing the issue of identity politics as a threat to the unity and harmony of the multicultural Indonesian people. Kompas.com puts identity politics in the form of straight news.